2015
DOI: 10.1007/s10639-015-9455-8
|View full text |Cite
|
Sign up to set email alerts
|

Selected aspects of conditions in the use of new media as an important part of the training of teachers in the Czech Republic and Poland - differences, risks and threats

Abstract: The paper presents the complex problems of preparation of pedagogy students to work as teachers in the context of their readiness to use ICT in the didactic process. The complexity of this subject matter has been proved by the current, ongoing, discussion about the direction of the expected transformations of contemporary schools and the prospective teachers education system in the age of prevalent digitization. Considering the complexity of conditions, the main research problem has been formulated as follows:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
1
18
0
3
Order By: Relevance
“…This is consistent with the findings of Brown (2017). Nevertheless, this is contrary to the findings on Czech and Polish students done by Tomczyk et al (2017), which revealed different attitudes toward applying digital solutions to the didactic process. Factors such as low evaluation of one's own competences or lack of evaluation in this area, lack of creative approach to the use of new media, lack of education in the area of new applications, lack of skills necessary to handle basic digital tools (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the findings of Brown (2017). Nevertheless, this is contrary to the findings on Czech and Polish students done by Tomczyk et al (2017), which revealed different attitudes toward applying digital solutions to the didactic process. Factors such as low evaluation of one's own competences or lack of evaluation in this area, lack of creative approach to the use of new media, lack of education in the area of new applications, lack of skills necessary to handle basic digital tools (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…The data analysis revealed that there is a group of teachers who obtained much higher test results because of their attitudes towards new media. Thus, techno-optimists are much more informed than techno-pessimists (Tomczyk et al 2015). Teachers who regularly use ICT in their classes, use e-textbooks, or think that new media facilitate greater engagement for their students, obtained statistically higher results.…”
Section: Discussionmentioning
confidence: 99%
“…From these results can be concluded if every teacher has skills in using the media then the competence of the teacher also increases. This is as said by Tomezyk et al where the professionalism of a teacher can be seen from the skills in using the media learning [8]. It is said that even a competent teacher when mastering media lessons and can use variations of instructional media in the classroom.…”
Section: A Effect Of Media Skills (X1) On Teacher Competence (Y)mentioning
confidence: 88%